Outcomes of Reoperative Valve Replacement in Patients with Prosthetic Valve Endocarditis: A 20-Year Experience - Young Woong Kim (Korean Journal of Thoracic and Cardiovascular Surgery, 2018)
Background: Prosthetic valve endocarditis (PVE) is a serious complication of cardiac valve replacement, and many p atients with P VE r equire r eoperation. The aim of t his study was to r eview our institutional 2 0 -year experience of surgical reoperative valve replacement in patients with PVE. Methods: A retrospective study was performed on 84 patients (mean age, 54.8±12.7 years; 51 males) who were diagnosed with PVE and underwent reoperative valve replacement from January 1995 to December 2016. Results: PVE was found in 1 valve in 61 cases (72.6%), and in 2 or more valves in 23 cases (27.4%). The median follow-up duration was 47.3 months (range, 0 to 250 months). Postoperative complications occurred in 39 patients (46.4%). Reinfection occurred in 6 cases, all within 1 year. The freedom from reinfection rate at 5 years was 91.0%±3.5%. The overall survival rates at 5 and 10 years were 64.4%±5.8% and 54.3%±7.3%, respectively. In stepwise multivariable Cox proportional hazard models, older age (hazard ratio [HR], 1.48; 95% confidence interval [CI], 1.05 to 2.10; p=0.027) and cardiopulmonary bypass (CPB) time (HR, 1.03; 95% CI, 1.00 to 1.0 1; p =0 . 0 33) e merged a s independent risk f actors f or d eath. Conclusion: Older age and a longer CPB time were associated with an increased risk of overall mortality in PVE patients.